Analisis Framing Pemberitaan Reynhard Sinaga Pada Media Online Tribunnews - Rico Fathur Nur Rohman; Nurul Hasfi (Interaksi Online, 2021)
Reynhard Sinaga became point of attention in mass media in early 2020, including for Tribunnews.com. Tribun sees reynhard's case as worthy/important news because of the factors of harassment cases with many victims and supported by the sexual orientation of Reynhard that is incompatible with the eastern culture of indonesia. In this study a total of 16 news items were selected for sample. The news taken from the reporting period which conducted by Tribunnews.com in January-April 2020 with a total of 50 more news items related to Reynhard. The 16 selected news items will be analyzed using zhongdang pan and Gerald M Kosicki model analysis. This study analyzed the media side of Tribunnews.com in campaigning the case of Reynhard Sinaga. It is known that Reynhard had a sexual orientation of being a gay in his life.Then, the writer will find out what the depiction of the news published by the Tribunnews when reporting the case. The results of the study found that the Tribunnews.com as a media in each of their news or report shows a negative tendency towards Reynhard Sinaga. The pattern of campaign always puts the negative side of Reynhard Sinaga to be displayed, regardless of his crime, his chosen orientation, problems with his family, and humiliating the State of Indonesia. Reynhard Sinaga's emphasis on sexual orientation is the source or basis of the news made by Tribunnews.com. Tribun's policy when preaching Reynhard was influenced by his editorial policy, and saw the majority of Indonesians as Muslim. Where it would be difficult to find a reader if tribun applied the neutrality side in the news.